Improvement of the Efficiency of TiO2 Photocatalysts with Natural Dye Sensitizers Anthocyanin for the Degradation of Methylene Blue: Review - Pujiastuti, Hendrini; Kustiningsih, Indar; Slamet, Slamet (Jurnal Rekayasa Kimia & Lingkungan, 2021)
One of the potential methods utilized for dye degradation is photocatalitic, due to its low cost, highly effective, and environmentally friendly. Effectivenes of TiO2 photocatalysts can be enhanced by adding a dye sensitizer. Dye-sensitizer material absorbs visible light to facilitate electron excitation process. Addition of dye-sensitizer on TiO2 photocatalyst promotes it to be more responsive to visible light. Natural anthocyanin dyes are often used as sensitizers of TiO2 semiconductors. Anthocyanins are, usually in the purple to the red color range, a group of natural dyes found in the flowers, leaves, and fruit of plants. The essential principles of dye sensitization to TiO2 have been explored in this review. It is feasible to reduce the band gap energy in the TiO2 photocatalyst by modifying it using a natural dye sensitized modification. Dye sensitizers on TiO2 nanotubes plate have the potential to be employed in a dye degradation photocatalytic system